Wheat grain moxibustion ameliorates oxidative stress in PTU-induced hypothyroid rats via cAMP/PKA pathway activation - Qin, Jing; Liu, Tingting; Zhang, Xiangyue; Chen, Xueni; Qin, Jie; Aslam, Muhammad Shahzad; Feng, Huimin; Zhang, Yanhui; Wang, Xiaoxu; Zhang, Tiansheng; Hao, Chongyao (Frontiers in Endocrinology, 2025)
BackgroundHypothyroidism is a systemic hypometabolic disorder characterized by thyroid hormone deficiency and is closely associated with oxidative stress. The cAMP/PKA signaling pathway is critically involved in regulating thyroid hormone secretion and reducing oxidative stress. This study investigates whether wheat grain moxibustion alleviates hypothyroidism in a hypothyroidism model by attenuating oxidative stress and activating the cAMP/PKA signaling pathway.MethodsThe hypothyroid rat model was established by administering propylthiouracil. Following wheat grain moxibustion treatment, rat general condition, behavioral performance, and thyroid function were assessed. Then thyroid tissues and serum samples were collected. Thyroid tissue microstructure was examined by hematoxylin-eosin staining. Serum levels of triiodothyronine, thyroxine, thyroid-stimulating hormone, free triiodothyronine, free thyroxine, reactive oxygen species, malondialdehyde, catalase, superoxide dismutase, glutathione peroxidase, and cAMP were quantified using ELISA. Protein expression of signaling pathway components was detected via WB, while corresponding mRNA levels were measured by RT-PCR. To clarify the relationship between cAMP/PKA signaling and oxidative stress, the PKA inhibitor H-89 was administered to a subset of wheat grain moxibustion-treated rats.ResultsWheat grain moxibustion treatment ameliorated the general condition, behavioral performance, and thyroid hormone profiles in propylthiouracil-induced hypothyroid rats. Furthermore, it significantly reduced serum levels of reactive oxygen species and malondialdehyde, while enhancing the activities of catalase, superoxide dismutase, and glutathione peroxidase, collectively indicating attenuated oxidative stress. Concurrently, wheat grain moxibustion activated the cAMP/PKA pathway, demonstrated by elevated serum cAMP levels, downregulated phosphodiesterase 3A expression, upregulated PKA expression, and increased phosphorylation of CREB in thyroid tissues. Notably, pharmacological inhibition of this pathway with H-89 reversed the ameliorative effects of wheat grain moxibustion on oxidative stress.ConclusionWheat grain moxibustion ameliorates oxidative stress in a propylthiouracil-induced hypothyroid rat model, mediated through activation of the cAMP/PKA signaling pathway. These results indicate its potential therapeutic utility in hypothyroidism management and mitigation of oxidative injury.